Caring Community for Mental Health in Astambul Kota Village, Banjar Regency - Raziansyah Raziansyah; Yohana Agustina Sitanggang; Tiara Lani (Journal of Health Community Service, 2022)
Mental health is still a health problem for the world. Cases of mental disorders continue to increase and impact the decreasing human productivity in the long term. In humans, mental health is important because mental health is a form of people themselves, which means having an ability to live for independently, with family, and the surrounding people. Service Activities to Community are carried out in the Astambul Kota Village, Banjar Regency, South Kalimantan, from December 2021 to January 2022 started from licensing to 2 stages of implementation. The first stage is screening the community regarding their perception of people with Mental disorders (ODGJ). The second stage is evaluation and providing health education about MASDUL SEJIWA. The data were analyzed by the descriptive-analytical method. The screening results showed that many people who did not care about ODGJ avoided it when they met one and felt afraid when there was ODGJ around. In the second stage, the community was given mental health education about caring for ODGJ and how to deal with ODGJ so as not to be afraid and run. This Community Service Activities showed that the participants' knowledge of Mental Health was good of 27 people (67.5%). According to the target, the enthusiasm and attendance of the participants are 40 people (100%) who attended screening activities and mental health education. The whole community is expected to increase the caring for ODGJ and the formation of mental health cadres in the Astambul Kota health region area